Comparison of dexmedetomidine and fentanyl as local anesthetic adjuvants in spinal anesthesia: a systematic review and meta-analysis of randomized controlled trials - Sun S; Wang J; Bao N; Chen Y; Wang J (Dove Medical Press, 2017)
ShuJun Sun,1 JiaMei Wang,2 NaRen Bao,1 Ying Chen,1 Jun Wang1 1Department of Anesthesiology, First Affiliated Hospital, China Medical University, Shenyang, Liaoning, 2College of Life and Health Sciences, Northeastern University, Shenyang, Liaoning, China Purpose: To compare the effects of dexmedetomidine (Dex) and fentanyl as adjuvants to local anesthetics in spinal anesthesia. Methods: Two researchers independently searched the PUBMED, EMBASE, Cochrane library, and CBM for randomized controlled trials comparing the effects of Dex and fentanyl as adjuvants to local anesthetics for intrathecal injection. Results: A total of 639 patients from nine studies were included in this meta-analysis. The results showed that Dex resulted in statistically significant longer duration of stable sensory block (mean difference [MD] =27.12; 95% confidence interval [CI] [9.89, 44.34], P<0.01, I2=97%), sensory block (standardized mean difference [SMD] =3.81; 95% CI [2.35, 5.27], P<0.01, I2=97%), motor block (SMD =3.64; 95% CI [2.19, 5.08], P<0.01, I2=97%), and pain free period (SMD =2.98; 95% CI [1.69, 4.27], P<0.01, I2=96%); reducing the incidence of pruritus (relative risk [RR] =0.15; 95% CI [0.06, 0.39], P<0.01, I2=0%) compared with fentanyl. However, the onset of sensory and motor block, the time to peak sensory level, and the incidence of hypotension and bradycardia, and the side effects (nausea, vomiting, shivering and respiratory depression) were not significantly different between Dex and fentanyl. Conclusion: Compared to fentanyl, Dex as local anesthetics adjuvant in spinal anesthesia prolonged the duration of spinal anesthesia, improved postoperative analgesia, reduced the incidence of pruritus, and did not increase the incidence of hypotension and bradycardia. Keywords: dexmedetomidine, fentanyl, meta-analysis, spinal anesthesia